The interaction of a supersonic plasma jet containing nanoparticles with a substrate - Kravchenko, O.Yu.; Maruschak, I.S. (Вопросы атомной науки и техники, 2021)
In the framework of a multi-fluid axisymmetric hydrodynamic model, the interaction of a supersonic plasma jet containing nanoparticles with a flat substrate is investigated using computer simulation. In particular, the fluxes of nanoparticles on the substrate are studied at plasma inlet pressure P₀=1…100 Torr. The results show that a shock wave is formed near the substrate, which affects the energy of nanoparticles and their fluxes on the substrate. The width of the region along the radius, where the flow of nanoparticles onto the substrate is essential, depends on the plasma pressure in the jet. At large values of plasma pressure (P₀≥75 Torr) a cloud of nanoparticles with a sharp boundary is formedon the axis of the plasma jet near the substrate. Interacting with this cloud, nanoparticles moving in the plasma jet, lose directed energy and their flow on the substrate near the axis of the jet is zero.